2012
DOI: 10.1590/s0103-84782012001100002
|View full text |Cite
|
Sign up to set email alerts
|

Ação de fungos entomopatogênicos em larvas e adultos da mosca do figo Zaprionus indianus (Diptera: Drosophilidae)

Abstract: Ação de fungos entomopatogênicos em larvas e adultos da mosca do figo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The use of entomopathogenic fungi for pest management, especially as part of an Integrated Pest Management (IPM) strategy, combined with cultural and other methods has increased because of the reduction in available chemical control measures (Ansari et al, 2011;Beris et al, 2012;Pelizza et al, 2012;Svedese et al, 2012). It has however been previously shown that both temperature and water availability (water activity, a w ) are bottlenecks in the efficacy of entomopathogenic fungi against pests (Magan, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The use of entomopathogenic fungi for pest management, especially as part of an Integrated Pest Management (IPM) strategy, combined with cultural and other methods has increased because of the reduction in available chemical control measures (Ansari et al, 2011;Beris et al, 2012;Pelizza et al, 2012;Svedese et al, 2012). It has however been previously shown that both temperature and water availability (water activity, a w ) are bottlenecks in the efficacy of entomopathogenic fungi against pests (Magan, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in South America, it became a serious threat and economic concern for fig growers, with losses of up to 50% of production in some groves (Svedese et al. ). Although there is some question as to whether they can act as primary pests in undamaged fruit while the fruit is on plants (Steck ), they have been reared from ripe or damaged grapes collected from the ground and also directly from the plant (Van Timmeren and Isaacs ).…”
Section: Introductionmentioning
confidence: 99%
“…As Z. indianus expands its range, an increasing variety of fruits are used as larval hosts (Lachaise and Tsacas 1983;van der Linde et al 2006), making Z. indianus of potential concern as a new pest of numerous tropical and temperate fruit crops. For example, in South America, it became a serious threat and economic concern for fig growers, with losses of up to 50% of production in some groves (Svedese et al 2012). Although there is some question as to whether they can act as primary pests in undamaged fruit while the fruit is on plants (Steck 2005), they have been reared from ripe or damaged grapes collected from the ground and also directly from the plant (Van Timmeren and Isaacs 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The captured flies were then placed in Erlenmeyers flasks, well-sealed with fine webbing. Based on the methodology of Svedese et al (2012), a source of food for the dipterans and cotton moistened with water to maintain humidity in the flask were added to promote survival conditions for the duration of the experiment. They were divided into two groups: groups of adults flies treated with AC001 (treated group) and groups that did not receive treatment (control group).…”
Section: Trialmentioning
confidence: 99%